2017
DOI: 10.1523/jneurosci.2733-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Long-Term Locomotor Memories Is Associated with Functional Connectivity Changes in the Cerebellar–Thalamic–Cortical Network

Abstract: Although motor adaptation is typically rapid, accumulating evidence shows that it is also associated with long-lasting behavioral and neuronal changes. Two processes were suggested to explain the formation of long-term motor memories: recall, reflecting a retrieval of previous motor actions, and faster relearning, reflecting an increased sensitivity to errors. Although these manifestations of motor memories were initially demonstrated in the context of adaptation experiments in reaching, indications of long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…After-effects were computed as the averaged value for each gait parameter over the first thirty strides of post-adaptation. We used 30 strides, rather than only the initial 1–5 strides, because we were interested in characterizing long lasting after-effects (Long et al, 2015; Roemmich and Bastian, 2015; Mawase et al, 2017). We removed baseline biases from both measures by subtracting the baseline values for each gait parameter averaged over the last 40 strides during baseline (minus the very last transient 5 strides).…”
Section: Methodsmentioning
confidence: 99%
“…After-effects were computed as the averaged value for each gait parameter over the first thirty strides of post-adaptation. We used 30 strides, rather than only the initial 1–5 strides, because we were interested in characterizing long lasting after-effects (Long et al, 2015; Roemmich and Bastian, 2015; Mawase et al, 2017). We removed baseline biases from both measures by subtracting the baseline values for each gait parameter averaged over the last 40 strides during baseline (minus the very last transient 5 strides).…”
Section: Methodsmentioning
confidence: 99%
“…Lesions affecting the anterior lobe vermal lobules I-III as well as posterior lobules VIII and IX can result in balance and gait instability [ 42 ]. Clinically, balance and gait disability are a common secondary condition following cerebral ischemia [ 44 - 53 ], and could potentially be reflected in the present observation of distal neurodegeneration in the cerebellum seen in our TGI NHPs.…”
Section: Discussionmentioning
confidence: 80%
“…A topographic study has revealed anatomical and functional hallmarks of specific cerebellar lobules [ 42 ]. Lobule III, a key component in the anterior lobe of the cerebellum, is predominantly responsible for leg and foot sensorimotor function [ 42 - 44 ]. Meanwhile, lobule IX is located in the posterior cerebellar lobe and functions in the visual guidance of movement, thereby utilizing visual information to direct movements and adjust reflexes appropriately [ 42 - 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…After-effects were computed as the averaged value for each gait parameter over the first thirty strides of post-adaptation. We used 30 strides, rather than only the initial 1 to 5 strides, because we were interested in characterizing long lasting after-effects (Long et al, 2015; Mawase et al, 2017; Roemmich and Bastian, 2015). We removed baseline biases from both measures by subtracting the baseline values for each gait parameter averaged over the last 40 strides during baseline (minus the very last transient 5 strides).…”
Section: Methodsmentioning
confidence: 99%